2017
DOI: 10.17576/akad-2017-8702-10
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Psychometric Properties of Malay Translated Religious Orientation Scale-Revised among Malaysian Adult Samples

Abstract: Religious Orientation Scale-Revised (ROS-R) has been used increasingly as an important measure in psychology of religion based researches and widely administered in cross-cultural settings. Unfortunately, there is no valid and reliable ROS-R available in reliability testing was performed to determine the internal consistency of the items which was achieved using Cronbach's Alpha coefficient method (α). The factor loading consisted of three factors with a total variance of 64.76%. The final version of M-ROS-R c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Higher scores indicate higher levels of a specific religious orientation. The ROS-R has been translated to Malay and reported to have satisfactory psychometric properties for use among adults in Malaysia [ 19 ]. In this study, the internal consistency Cronbach alpha was reported at 0.71.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate higher levels of a specific religious orientation. The ROS-R has been translated to Malay and reported to have satisfactory psychometric properties for use among adults in Malaysia [ 19 ]. In this study, the internal consistency Cronbach alpha was reported at 0.71.…”
Section: Methodsmentioning
confidence: 99%
“…Z hlediska teoretických přístupů u problematiky vězeňského násilí je vlivná teorie vězeňské subkultury, která předpokládá, ţe násilí je časté tam, kde je skupinou povaţováno za hodnotu a kde jeho uplatnění vede v určitých situacích ke zvýšení statusu jedince, klade důraz na maskulinitu, nepoddajnost, hrdost, odpor a revoltu (Kamaluddin et al 2016). Především muţské věznice jsou povaţovány za maskulinní prostředí, kde je bodybuilding (posilování, zvyšování muskulatury) do jisté míry součástí vyplnění volného času odsouzených.…”
Section: Vězeňské Násilí a Projevy Agresivního Chováníunclassified
“…This research was carried out in the Malays language and the report is written in English for knowledge-sharing purposes. Translation from Malays Language and English was done using the "Forward and backward" translation technique (Brislin, 1970;Kamaluddin et al, 2017) by coders proficient in both languages.…”
Section: Measurementioning
confidence: 99%